Modelling Urea and Creatinine Concentration Distribution in Hollow Fiber Membranes for Hemodialysis Applications - Fauziah, Melinda Nur; Nurkhamidah, Siti; Taufany, Fadlilatul; Altway, Ali; Susianto; Rahmawati, Yeni (Eksergi, 2025)
Humans are dynamic creatures who continue to follow developments over time. This development also has a big impact on changes in habits and has an impact on the health of everyone, which needs special attention in this era of globalization. One of the treatments for kidney failure patients is kidney function replacement therapy, namely haemodialysis. Haemodialysis therapy is a high technology to replace the function of the kidneys in removing metabolic waste (air, sodium, potassium, hydrogen, urea, creatinine, uric acid and other substances) through a semi-permeable membrane as a separator for blood and dialysate fluid in an artificial kidney (dialyzer). where the processes of diffusion, osmosis, and ultrafiltration occur. In this study, a hollow fiber type dialyzer was used which consisting of three main components: the shell (which directs dialysate flow), the porous membrane, and the tube (which carries blood). In general, this research will be carried out theoretically by developing a mathematical model of mass transfer in hollow fiber membranes in the haemodialysis process to study the distribution of urea and creatinine concentrations in the tube, membrane, and shell axial and radial section, the effect of pore area of membrane on urea and creatinine clearance, and the influence of dialysate flowrate on urea and creatinine clearance. The mathematical modeling successfully illustrates the distribution of urea and creatinine concentrations within the hollow fiber membrane both axially and radially, with a concentration decrease from blood to dialysate, influenced by diffusion and convection mechanisms. Simulation results indicate that increasing dialysate flowrate enhances haemodialysis efficiency, but its effect diminishes after reaching a certain threshold. Meanwhile, increasing the membrane surface area from 1.3 m² to 1.8 m² results in only a slight reduction in the urea concentration from 16.67 mol/m³ to 16.62 mol/m³ and creatinine from 8.85 mol/m³ to 8.83 mol/m³, demonstrating that membrane surface area has a smaller impact.